2012
DOI: 10.1177/0044118x12471355
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal Development and Sexual Intercourse Among Adolescent Girls

Abstract: There are strong reasons to assume that early onset of puberty accelerates coital debut among adolescent girls. Although many studies support this assumption, evidence regarding the putative causal processes is limited and inconclusive. In this research, longitudinal data from the 1986 Northern Finland Birth Cohort Study (N = 2,596) were used to address three theoretical explanations: (a) a direct effect premised on biological processes, (b) a mediated path based on social psychological processes, and (c) a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 52 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…The specific effect was moderated by gender, such that positive prediction from CCR to risky sex was evident for girls but not boys. Developmental theory and etiological studies suggest that early exposure to risk may accelerate pubertal development (Belsky et al, 2010), and prior research has shown that early maturation is a risk factor for precocious sexual debut and risky sex behavior, particularly among girls (Savolainen et al, 2015). It is possible that this developmental process explains the specific effect of CCR on risky sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific effect was moderated by gender, such that positive prediction from CCR to risky sex was evident for girls but not boys. Developmental theory and etiological studies suggest that early exposure to risk may accelerate pubertal development (Belsky et al, 2010), and prior research has shown that early maturation is a risk factor for precocious sexual debut and risky sex behavior, particularly among girls (Savolainen et al, 2015). It is possible that this developmental process explains the specific effect of CCR on risky sex.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is unknown if CCR primarily has effects on general problem behavior or if it might also have specific effects on particular outcomes. For example, early adversity in the form of CCR might lead to accelerated pubertal development (Belsky, Houts, & Fearon, 2010), which is associated with earlier initiation of sexual activity and sex-risk behavior (Savolainen et al, 2015). These processes could result in a specific effect from early CCR to adolescent risky sex, over-and-above heightened risk for general problem behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of an association between menarche and intended reproductive timing in this sample is perhaps not surprising given that this relationship tends to be indirect and mediated by sexual initiation (Udry, 1979;Andersson-Ellströ m et al, 1996;Deardorff et al, 2005;Dunbar et al, 2008;Savolainen et al, 2012). Although it is possible that some of the sample were sexually active it is likely to be only a small proportion.…”
Section: Discussionmentioning
confidence: 74%
“…In terms of menarche, neighbourhood-level adversity has been largely ignored. If one considers that associations between early menarche and early childbearing in females have been directly (Dunbar et al, 2008) and indirectly (Udry, 1979;Helm & Lidegaard, 1990;Andersson-Ellströ m et al, 1996;Deardorff et al, 2005;Savolainen et al, 2012) found in the literature, it is plausible that neighbourhood-level factors could also play a role in menarche. Women living in neighbourhoods with higher levels of disadvantage (McCulloch, 2001;Nettle, 2010) and mortality rates (Wilson & Daly, 1997), decreased life expectancies, fewer healthy years (Nettle, 2011) and lower perceptions of safety (Johns, 2011) tend to have younger ages at first birth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation